Criticism of Islamic Law on the Application of the Principle of Restorative Justice in Handling Corruption Cases and its Relevance to Jampidsus Circular Letter No. B-1113/F/Fd.1/05/2010 - Sungguh, Hardi Muhar; Ulum, Bahrul; Harun, Hermanto (International Journal of Advanced Multidisciplinary, 2025)
This study aims to critically examine the application of the restorative justice principle in the handling of corruption crimes (tipikor) in Indonesia, particularly as facilitated by the Circular Letter of the Deputy Attorney General for Special Crimes (JAMPIDSUS) No. B-1113/F/Fd.1/05/2010. Although restorative justice emphasizes restitution and participatory resolution, its implementation in corruption cases raises serious concerns regarding substantive justice, legal certainty, and the potential for impunity. This research adopts a normative juridical approach, employing Islamic legal principles as an analytical framework to assess the alignment of restorative justice with the core values of Islamic law, including justice (‘adl), public interest (ma?la?ah), and the prevention of wrongdoing (zajr). Initial findings indicate that restorative justice, when applied loosely and without strict boundaries or adequate sanctions, may conflict with Islamic legal values, especially in the context of corruption, which is categorized as an extraordinary crime. Therefore, this study aims to formulate a model for the application of restorative justice that is fair, proportional, and aligned with maq??id al-shar?‘ah, thereby contributing to the reform of Indonesia’s criminal law system.